Interleukin-10 Facilitates Glutamatergic Synaptic Transmission and Homeostatic Plasticity in Cultured Hippocampal Neurons - Nenov, Miroslav N. (Int J Mol Sci, 2019)
Anti-inflammatory cytokines are known to exert neuroprotective action ameliorating aberrant neuronal network activity associated with inflammatory responses. Yet, it is still not fully understood if anti-inflammatory cytokines play a significant role in the regulation of synaptic activity under normal conditions. Thus, the aim of our study was to investigate the effect of Interleukin-10 (IL-10) on neuronal synaptic transmission and plasticity. For this we tested the effect of IL-10 on miniature excitatory postsynaptic currents (mEPSC) and intracellular Ca(2+) responses using whole-cell patch clamp and fluorescence microscopy in 13–15 DIV primary hippocampal neuroglial culture. We found that IL-10 significantly potentiated basal glutamatergic excitatory synaptic transmission within 15 min after application. Obtained results revealed a presynaptic nature of the effect, as IL-10 in a dose-dependent manner significantly increased the frequency but not the amplitude of mEPSC. Further, we tested the effect of IL-10 on mEPSC in a model of homeostatic synaptic plasticity (HSP) induced by treatment of primary hippocampal culture with 1 µM of tetrodotoxin (TTX) for a 24 h. It was found that 15 min application of IL-10 at established HSP resulted in enhanced mEPSC frequency, thus partially compensating for a decrease in the mEPSC frequency associated with TTX-induced HSP. Next, we studied if IL-10 can influence induction of HSP. We found that co-incubation of IL-10 with 1 µM of TTX for 24 h induced synaptic scaling, significantly increasing the amplitude of mEPSC and Ca(2+) responses to application of the AMPA agonist, 5-Fluorowillardiine, thus facilitating a compensatory postsynaptic mechanism at HSP condition. Our results indicate that IL-10 potentiates synaptic activity in a dose- and time-dependent manner exerting both presynaptic (short-term exposure) and postsynaptic (long-term exposure) action. Obtained results demonstrate involvement of IL-10 in the regulation of basal glutamatergic synaptic transmission and plasticity at normal conditions.